Anthropometrically Determined Undernutrition among the Adolescent Girls in Kathmandu Valley - Shrestha, B. (Kathmandu University Medical Journal, 2017)
Background No information exists regarding the health of the adolescent girls residing in Kathmandu valley in urban setup. Objective To evaluate the prevalence of undernutrition among the adolescent girls living in Kathmandu valley. It also aims to know the distribution of weight, height and body mass index of adolescent girls in relation to the different adolescent age groups. Method A cross sectional study was conducted in one government and two private schools in Kathmandu valley from 16th April to 15th September 2010. Anthropometric measurements were recorded using standardized methodology as recommended by World Health Organization (WHO). Standard operational definitions like percentiles, mean, standard deviation and proportions were used for analysis. Result Four hundred adolescent girls were enrolled randomly, out of which 111 girls (27.8%) were from government school and 289 girls (72.2 %) were from private schools. Maximum were of 16 years of age and the least were of 19 years of age, mean age being 15.4 years of age. Of them, early, mid and late adolescents were 41%, 35% and 24% respectively. Around one third of the study population were stunted (32%), one fourth were underweight (24%) and one tenth of them were thin (9.5%) based on National Center for Health Statistics (NCHS )standard. Both underweight and stunted girls were significantly more during the late adolescence period (P<0.001). However, thinness was not significant in any of the three adolescent age groups. Conclusion A high prevalence of undernutrition in terms of stunting, underweight and thinness exists among the adolescent girls in Kathmandu valley.